2022
DOI: 10.1007/s10549-022-06757-3
|View full text |Cite
|
Sign up to set email alerts
|

Routine and interval detection of locoregional breast cancer recurrences and risk of subsequent distant metastasis

Abstract: Purpose Follow-up for breast cancer survivors consists of after care and surveillance. The benefits of routine surveillance visits remain debatable. In this study we compared the severity of locoregional recurrences (LRRs) and the subsequent risk of a distant metastasis (DM) between LRRs detected at routine and interval visits. Methods Women diagnosed with early breast cancer between 2003 and 2008 in one of the 15 participating hospitals, and who developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…One study reported no significant relationship between the way of detection (i.e. routine visits or symptomatic discovery) of the LRR and the grade and stage of the LRR or the risk of DM, further underlining the de-escalation of follow-up [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported no significant relationship between the way of detection (i.e. routine visits or symptomatic discovery) of the LRR and the grade and stage of the LRR or the risk of DM, further underlining the de-escalation of follow-up [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have previously evaluated guideline adherence and mainly reported a higher than recommended intensity of follow-up related to the application of radiotherapy, patient preferences, financial incentives and inadequate intervals, irrespective of patients’ individual risk of recurrence [ 11 13 ]. Additionally, nearly half of all recurrences are found by patients themselves between routine visits and are of similar severity as recurrences detected at routine visits [ 7 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, MECs without any of the aforementioned characteristics, breast‐conserving surgery with clear margins would suffice to avoid overtreatment 64–66 . In both scenarios, it is wise to adopt tailored follow‐up procedures 67–69 . Similarly, the de‐escalation of adjuvant medical treatment, including chemotherapy, immunotherapy, targeted therapies, and radiotherapy requires a multidisciplinary approach 70–72 .…”
Section: Discussionmentioning
confidence: 99%
“… 64 , 65 , 66 In both scenarios, it is wise to adopt tailored follow‐up procedures. 67 , 68 , 69 Similarly, the de‐escalation of adjuvant medical treatment, including chemotherapy, immunotherapy, targeted therapies, and radiotherapy requires a multidisciplinary approach. 70 , 71 , 72 Hence, the paucity of comprehensive molecular information on large cohorts of patients prevents any specific recommendation and thus, our results should be validated and discussed in the context of multi‐institutional studies and dedicated cancer registries.…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, one in seven women is diagnosed with breast cancer at some point in their lives (Eijkelboom et al, 2020). Early diagnosis, for example by the national screening programme, and improved treatment have increased the survival rates over the years (Netherlands Cancer Registry, 2021).…”
Section: Introductionmentioning
confidence: 99%